Technology-Based Education Innovation and Multicultural Approach to Students' Character Development and Social Competence - Zaenudin; Wafik Aziza (Universitas Pendidikan Ganesha, 2025)
The development of digital technology and cultural diversity presents both challenges and opportunities in education. This condition requires the development of transformative learning strategies to optimally shape students’ character and social competence. However, in practice, educational policies have not yet fully supported the comprehensive integration of technology and multicultural approaches. This study aims to analyze the influence of technology-based educational innovations and multicultural approaches on the development of students’ character and social competence. The research employed a quantitative method with a correlational design involving 57 teachers from elementary, junior high, and high school levels as respondents. Data were collected through a 24-item questionnaire and analyzed using multiple linear regression and the Mann-Whitney test. The results showed that technology-based education (X₁) and multicultural approaches (X₂) simultaneously contributed significantly to student character development (Y₁) by 79.5% (R² = 0.795) and student social competence (Y₂) by 74.7% (R² = 0.747). Furthermore, the Mann-Whitney test identified no significant differences in the application of educational technology between primary and secondary levels. These findings recommend the need for synergistic integration of technology and multicultural approaches in the learning process to comprehensively optimize students’ character and social competence. The educational implication of this study is that policymakers and practitioners should design curricula and learning strategies that consistently integrate the use of technology with multicultural values, thereby creating an inclusive, adaptive, and globally relevant learning environment.